Re-structuring hedges: Rejuvenation management can improve the long term quality of hedgerow habitats for wildlife in the UK. (June 2015) - Staley, Joanna T.; Amy, Sam R.; Adams, Nigel P.; Chapman, Roselle E.; Peyton, Jodey M.; Pywell, Richard F.
Highlights: Hedgerows benefit wildlife if in good condition with a dense structure. Traditional hedge-laying rejuvenation is quite expensive and not commonly used. A multi-site field experiment tested five rejuvenation methods over three years. Cheaper, modern alternatives improved hedge structure and berry provision. Conservation hedging could double the length of hedgerow that is rejuvenated. Abstract: Hedgerows provide key wildlife habitat in intensive agricultural landscapes, but are declining in length and structural condition due to a lack of rejuvenation management, neglect and over-frequent trimming with mechanised flails. Here, we test cheaper, alternative methods to traditional hedge laying methods using a multi-site manipulative field experiment. In the first quantitative test of new approaches to hedge rejuvenation management, hedge regrowth, structure, berry provision for over-wintering wildlife and cost of rejuvenation were assessed in response to five methods, for three years following rejuvenation. Three 'laying' methods and coppicing were effective at improving hedgerow condition by stimulating basal regrowth, thus increasing the density of woody material at the base and reducing gap size. The pros and cons of coppicing are discussed in relation to its impact on different wildlife groups, and it is recommended in limited circumstances. Differences between the three 'laying' methods reduced over time, so a cheaper conservation hedging method is recommended as an alternative to traditional hedge laying. This new approach to hedge management offers the potential to restore twice the length of hedgerow currently rejuvenated under agri-environment schemes.